THE INFLUENCE OF SERVICE AND TASTE OF CAFE UNI IN PADANG PARIAMAN - Nurofik, Agus; Nini, Nini; Permana, Hendrik; Indrayani, Tri Irfa (PT. Altin Riset Publishing, 2025)
This study aims to analyze the quality of service and the taste of food at Cafe Uni, a café that serves traditional regional dishes with authentic interior design and cultural atmosphere. The focus of the research is on how Cafe Uni maintains taste consistency despite the challenge of limited availability of spices, as well as how its service strategies create customer satisfaction and loyalty. This approach is relevant given that culture-based culinary businesses have great potential to attract market interest while preserving tradition. The research employed a qualitative approach, with data collected through in-depth interviews with the owner and staff of Cafe Uni, as well as direct on-site observations. Data analysis was conducted using a descriptive qualitative method, linking field findings to relevant theories such as the SERVQUAL model for service quality, the expectancy-disconfirmation model for customer satisfaction, and the concept of experiential marketing for dining experiences. The findings reveal that Cafe Uni successfully preserves authentic flavors by sourcing spices directly from their regions of origin, either through staff traveling home or via cargo shipments. The quality of ingredients is maintained through proper temperature-controlled storage to preserve their color and texture. Friendly, smiling, and interactive service creates a welcoming atmosphere for customers, even for those dining alone. The integration of authentic taste, quality service, and cultural ambiance significantly enhances customer satisfaction and fosters repeat visits. This study provides practical insights for regional culinary business owners in managing unique dining experiences to remain competitive in the market.